Castration remains despite decreasing definitive treatment of localized prostate cancer in the elderly: A case for de‐implementation. Issue 20 (7th September 2018) - Skolarus, Ted A.; Caram, Megan EV; Chapman, Christina H.; Smith, David C.; Hollenbeck, Brent K.; Hawley, Sarah; Tsodikov, Alexander; Sales, Anne; Wittmann, Daniela; Zaslavsky, Alexander
Abstract : Maximizing the quality and quantity of life among men with localized prostate cancer who are elderly and have competing comorbidities may be achieved more effectively, either by treating these patients definitively or by opting for observation rather than using primary androgen‐deprivation therapy. A better understanding of the optimal ways to de‐implement this low‐value cancer care appears to be warranted for both elderly patients, who have little to gain by it, and younger patients, who have more to lose by foregoing definitive treatment with surgery or radiation therapy.